Single-Crystalline InGaAs Nanowires for Room-Temperature High-Performance Near-Infrared Photodetectors - Tan, Huang; Fan, Chao; Ma, Liang; Zhang, Xuehong; Fan, Peng; Yang, Yankun; Hu, Wei; Zhou, Hong; Zhuang, Xiujuan; Zhu, Xiaoli; Pan, Anlian (Nano-Micro Letters, 2015)
InGaAs is an important bandgap-variable ternary semiconductor which has wide applications in electronics and optoelectronics. In this work, single-crystal InGaAs nanowires were synthesized by a chemical vapor deposition method. Photoluminescence measurements indicate the InGaAs nanowires have strong light emission in near-infrared region. For the first time, photodetector based on as-grown InGaAs nanowires was also constructed. It shows good light response over a broad spectral range in infrared region with responsivity of 6.5 × 103 A W−1 and external quantum efficiency of 5.04 × 105 %. This photodetector may have potential applications in integrated optoelectronic devices and systems.